Self-sensing of soil-cement composites based on carbon nanotubes for civil engineering monitoring - Vasconcelos, Ana Raina Carneiro (2024)
Civil infrastructures are sometimes exposed to a dynamic and complex environment, accelerating their deterioration over time. Cracks, fissures, and reduction in structural integrity becomes inevitable. Early detection of the damage location and size is crucial to prevent catastrophic failures. As a result, different smart and self-sensing materials in civil structural monitoring have become the object of study in recent years, with carbon nanotubes emerging as particularly promising. The integration of carbon nanotubes into composite materials enhances self-sensing properties, which are already widely utilized for monitoring stress and strain through electrical responses. However, overcoming the challenges posed by the high aspect ratio and Van der Waals forces of the carbon nanotubes to achieve uniform distribution and stability for composites remains a significant hurdle. By ensuring dispersion and uniformity within composites, the potential arises to transform them into efficient smart materials for Structural Health Monitoring, through the analysis of electrical properties and detection of soil-cement composites. In this way, it is proposed in this dissertation the development of self-sensing soil-cement composites incorporating carbon nanotubes for monitoring. Physicochemical characterization techniques were employed to ensure the efficiency and stability of multi-walled carbon nanotubes dispersion in superplasticizer admixtures and soil-cement composites. Subsequently, the electrical properties were investigated using the two-probe method in soil-cement samples. The obtained results demonstrate promising outcomes regarding the effective role of superplasticizer admixture in enhancing dispersion and ensuring structural stability throughout the useful life of dispersions and composites containing carbon nanotubes. Furthermore, the dissertation highlights the electrical and sensing properties of these smart composites, noting increases in resistivity during the cure process. However, it's noted that the fixed quantity of carbon nanotubes did not reach the percolation threshold, thereby failing to achieve more significant electrical values. The findings establish a solid and positive indications for the development of selfsensing soil-cement composites based on carbon nanotubes for employment as strain-stress monitoring in civil engineering.